The oxygen vacancy in Li-ion battery cathode materials. Issue 11 (7th September 2020) - Tang, Zhen-Kun; Xue, Yu-Feng; Teobaldi, Gilberto; Liu, Li-Min
Abstract : Oxygen vacancies can promote Li-ion diffusion, reduce the charge transfer resistance, and improve the capacity and rate performance of Li-ion batteries. However, oxygen vacancies can also lead to accelerated degradation of the cathode material structure, and lead to phase transition etc . Abstract : The substantial capacity gap between available anode and cathode materials for commercial Li-ion batteries (LiBs) remains, as of today, an unsolved problem. Oxygen vacancies (OVs) can promote Li-ion diffusion, reduce the charge transfer resistance, and improve the capacity and rate performance of LiBs. However, OVs can also lead to accelerated degradation of the cathode material structure, and from there, of the battery performance. Understanding the role of OVs for the performance of layered lithium transition metal oxides holds great promise and potential for the development of next generation cathode materials. This review summarises some of the most recent and exciting progress made on the understanding and control of OVs in cathode materials for Li-ion battery, focusing primarily on Li-rich layered oxides. Recent successes and residual unsolved challenges are presented and discussed to stimulate further interest and research in harnessing OVs towards next generation oxide-based cathode materials.